2008
DOI: 10.1002/anie.200802120
|View full text |Cite
|
Sign up to set email alerts
|

Multifunctionalized Ruthenium‐Based Supersensitizers for Highly Efficient Dye‐Sensitized Solar Cells

Abstract: Dye-sensitized solar cells (DSCs) have been explored for photovoltaic applications because of their low cost and impressive conversion efficiency.[1] A DSC with 10 % efficiency was first demonstrated by Grätzel and co-workers using N3 (cis-di(thiocyanato)bis(2,2'-bipyridyl-4,4-dicarboxylate) ruthenium(II)) as a sensitizer.[2] Progress in optimizing ruthenium-based sensitizers for DSCs has been focused primarily on enhancing the light-harvesting ability, and redshifting the metal-to-ligand charge transfer (MLCT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
107
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 185 publications
(111 citation statements)
references
References 33 publications
4
107
0
Order By: Relevance
“…Density functional theory (DFT) indicated that the methyl substituents in the xylyl bridge destabilized the planar configuration of the arylthiophene moiety by about 40 kJ mol -1 relative to the phenyl bridge. The extinction coefficients of the xylyl-bridged compounds were about half those with phenyl bridges, a behaviour that is also consistent with decreased conjugation 36,37 . Marcus-Hush analysis of the absorption spectra of the one-electron oxidized forms of these molecules revealed an approximate tenfold decrease in electronic coupling (H AB ) through the xylyl bridge.…”
Section: Discussionsupporting
confidence: 69%
“…Density functional theory (DFT) indicated that the methyl substituents in the xylyl bridge destabilized the planar configuration of the arylthiophene moiety by about 40 kJ mol -1 relative to the phenyl bridge. The extinction coefficients of the xylyl-bridged compounds were about half those with phenyl bridges, a behaviour that is also consistent with decreased conjugation 36,37 . Marcus-Hush analysis of the absorption spectra of the one-electron oxidized forms of these molecules revealed an approximate tenfold decrease in electronic coupling (H AB ) through the xylyl bridge.…”
Section: Discussionsupporting
confidence: 69%
“…In most cases, polypyridyl ruthenium complexes are likely choices for such applications [1][2][3][4]. While the complexes work reasonably well in visible light, the main drawback of such complexes is a lack of reasonable absorption in the near-IR region.…”
Section: Introductionmentioning
confidence: 99%
“…After the successful exploration by Grätzel and co-worker [1,10], DSSCs based on Ru-photosensitizers, such as N3 and N719, have been extensively investigated and developed [11,12]. So far, the impressive solar-toelectrical power conversion efficiency values of $11% have been reported for the Ru sensitizers [11][12][13][14][15][16]. However, in addition to high cost of rare Ru metal, the ruthenium dyes featuring relatively low molar extinction coefficients and tedious purification processes [12].…”
Section: Introductionmentioning
confidence: 99%